Determinação experimental da solubilidade de eletrólitos em solventes puros e misturas de solventes - Pires, Ricardo Francisco (2007)
The knowledge of the solubility of an electrolyte in a pure solvent, or in a mixture of solvent, is extremely important for many industrial applications and also in the design of industrial equipment. This knowledge can also be useful for the studies of modeling for the prediction of solubility data. In this work, the experimental solubility of an electrolyte, salt or acid, in a pure solvent or in a binary mixture of solvent, was obtained. Fourteen systems had been evaluated. Most of them presented only one liquid phase. However, there were some that two liquid phases was formed. The analysis of the liquid phase was made using the gravimetric method, as well as the titration. The measurements were carried out keeping the temperature constant and in atmospheric conditions. The apparatus used in this research consisted of two jacketed glass vessels, named cells, connected in series. The cells were linked by a latex line and connected to a thermostatic bath. Each cell was supported on a magnetic agitator. The temperature of the cells was controlled by circulating thermostated water in the jacket. Firstly, an amount of pure solvents were added in the cells. Secondly, an excess of electrolyte (acid or salt) was loaded, gravimetrically. After temperature stabilization, the period of stirring of the mixture was of one half hour and for the saline systems and 1 h for acid ones, followed of a settling time that lasted about 3 h for them leaves and 2 h for acid ones. Liquid phase was sampled by using a glass syringe. When the system presented the formation of two liquid phases, both were analyzed. Some results of pure electrolyte-solvent solubility had shown good agreement comparing to the literature. Original data of solubility had been taken experimentally. In general, most of solubility data decreased with temperature. Finally, the values of solubility in function of the temperature had been used to obtain the parameters of rational equations in literature useful to correlation of solubilities in function of the temperature.